2011
DOI: 10.1016/j.neurobiolaging.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Premarin dose-dependently enhances memory, affects neurotrophin protein levels and alters gene expression in middle-aged rats

Abstract: Premarin™ is the most commonly prescribed estrogenic component of hormone therapy, given since 1942. The current study is the first examining cognitive effects of tonic Premarin treatment in an animal model. Middle-aged ovariectomized (Ovx) rats received vehicle or one of three doses of Premarin (12, 24 or 36 μg daily). Rats were tested on a spatial working and reference memory maze battery. Both Medium- and High- dose Premarin enhanced memory retention, while Low-dose Premarin impaired learning and memory ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 123 publications
4
75
0
Order By: Relevance
“…Partly consistent with these findings, low-dose daily Premarin impaired spatial reference and working memory compared to ovariectomized controls in the working/reference memory version of the radial arm maze (45). High doses of tonic Premarin reduced the number of errors in a delayed matching to sample plus maze when a 6 h delay was introduced between trials 2 and 3 (153). Medium and high tonic Premarin doses also improved performance in the reference Morris Water Maze task (154).…”
Section: Estronementioning
confidence: 93%
See 1 more Smart Citation
“…Partly consistent with these findings, low-dose daily Premarin impaired spatial reference and working memory compared to ovariectomized controls in the working/reference memory version of the radial arm maze (45). High doses of tonic Premarin reduced the number of errors in a delayed matching to sample plus maze when a 6 h delay was introduced between trials 2 and 3 (153). Medium and high tonic Premarin doses also improved performance in the reference Morris Water Maze task (154).…”
Section: Estronementioning
confidence: 93%
“…Engler-Chiurrazzi et al [2011] gave tonic Premarin at levels analogous to low, medium, or high (time levels of the usual dose given to women (153). Low-dose tonic Premarin treatment impaired learning the Morris Water Maze (spatial reference memory) and the delayed-match-to-sample plus maze (spatial working memory), but had no significant effect in the working/reference memory version of a water radial arm maze (153). Partly consistent with these findings, low-dose daily Premarin impaired spatial reference and working memory compared to ovariectomized controls in the working/reference memory version of the radial arm maze (45).…”
Section: Estronementioning
confidence: 99%
“…NGF protein concentrations were assessed via enzyme-linked immunosorbent assay (ELISA) using commercially available kits from Promega (Madison, Wisconsin). NGF assay procedures were conducted as previously described (Engler-Chiurazzi, et al, 2009). Briefly, tissue lysates were made, processed, and read in flat-bottom 96 well plates according to the kit's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…This effect occurred specifically at the highest working memory load, where animals have the most items of information to remember; Ovx animals treated with MPA in middle-age also had impaired overnight forgetting on the MM, a measure of memory retention [124125]. Related research utilizing the Ovx model showed that, depending on dose, CEE benefited spatial working and reference memory after a delay in the WRAM and a delayed match-to-sample task (DMS), another common water escape task used to evaluate spatial working and recent memory [126]. …”
Section: 1 Evaluating Hormones Behavior and Brains In Rodent Menomentioning
confidence: 99%